TONGUE TWISTER AS AN ICE BREAKER IN BOOSTING STUDENTS’ SPEAKING ABILITY - Nopa Yusnilita; Nurul Afifah (Universitas PGRI Semarang, 2020)
This study discussed about how tongue twister effective in boosting students’ speaking ability at the tenth graders of MAN 1 OKU. To collect data, the researcher used test in the form of recording video as an instrument. The methodology of this research was experimental research and the researcher used Quasi experimental method. From the population, the researcher took class X.IPA3 and X.IPS 1 as samples of this research, where X.IPA 3 was as the experimental class, and X.IPS 1 as the control class. The total number of sample was 72. The samples were taken by using simple random sampling. The students’ mean score in pretest in control class was 4.66 while the pretest in experimental class was 6.49. The mean score in posttest in control class was 4.94 and the mean score of posttest in experimental class was 7.36. Based on the distribution of students’ score in pre-test and post-test Tongue Twister strategy was effective in boosting students’ speaking ability to the tenth Graders of MAN1 OKU because the students’ score in post-test was better than pre-test both in control class and experimental class, and the significant difference is seen in experimental class that is taught by tongue twister. The minimum scores in pre-test were 1.67 in each class, and and the maximum score were 6.94 and 8.33, while the minimum scores in post-test were 1.67 and 5, while the maximum score was 7.5 and 9.17. If the value of Sig. (2-tailed) = 0,000 more than the Significance level (a=0,05) it means that it was significantly effective to use Tongue Twister strategy in boosting students’ speaking ability at the tenth graders of MAN 1 OKU